Do Firms Manage Earnings to Influence Credit Ratings? Evidence from Negative Credit Watch Resolutions - Liu, Alfred Zhu; Subramanyam, K. R.; Zhang, Jieying; Shi, Charles (The Accounting Review, 2018)
ABSTRACT We investigate whether issuers on negative credit watch manage earnings upward and whether such earnings management favorably influences the watch resolution. We find that rating, industry, and performance matched discretionary accruals reported during negative watch are significantly higher than their respective pre- and post-watch levels, after controlling for accrual reversal. Consistent with its opportunistic nature, we find that accrual management increases with issuers' incentives to avoid downgrade, and decreases with their earnings management constraints and the strength of the external monitoring. Surprisingly, such accrual management significantly increases the likelihood of a favorable resolution—issuers in the top half of the discretionary accruals distribution are 24 percent less likely to be downgraded than those in the propensity score matched bottom half. We find that issuers that avoid downgrades through income-increasing accrual management significantly underperform those that do not over the ensuing year, mitigating the signaling or measurement error explanations for our results. Finally, we find that accrual management does not reflect attempts to improve short-term credit quality. JEL Classifications: M41; G29; G38.